Severe Factor V Deficiency with Prolonged Bleeding Time - Bkeederveld, Kees; van Royen, Eric A.; ten Cate, Jan W. (Thrombosis and Haemostasis, 1974)
A patient with two congenital defects, i.e. a severe factor V deficiency and an aortic coarctation is described. Arguments for a dominant mode of inheritance of the factor V deficiency are presented. A coinciding haemostatic defect consisting of a prolonged bleeding time, which could be corrected by fresh plasma and cryoprecipitate, and a decreased platelet retention in the glass bead test disappeared after surgical correction of the coarctation.Extensive platelet studies failed to show any further defect.